LEADERSHIP STYLE ANALYSIS IN ENHANCING EMPLOYEE PERFORMANCE AT THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF RIAU ISLANDS PROVINCE - Anggia Sekar Putri; Anoesyirwan Moeins; Marhalinda (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This research aims to understand the leadership styles in enhancing employee performance at the General Bureau of the Regional Secretariat of Riau Islands Province. This study employs a descriptive research design with a qualitative approach. The data collection methods employed in this study are observation, interviews, and documentation. Data processing is carried out through data reduction, data presentation, and drawing conclusions based on the research findings. As for data analysis, data credibility testing is conducted to ensure the validity of the data, utilizing source triangulation. Based on the findings of this research, it is evident that the democratic leadership style implemented at the General Bureau of the Regional Secretariat of Riau Islands Province has successfully enhanced employee performance. This is apparent through the well-established leader-subordinate relationships, clear task structures aligned with the subordinates' abilities, and the provision of authority to discipline subordinates in accordance with regulations. As a result, subordinates are motivated to work diligently and meticulously, leading to an improvement in their performance. However, there is still room for improvement in the relationships among employees to foster a more positive environment.